2017
DOI: 10.1016/j.jpeds.2016.12.059
|View full text |Cite
|
Sign up to set email alerts
|

The Randomized, Controlled Trial of Late Surfactant: Effects on Respiratory Outcomes at 1-Year Corrected Age

Abstract: Objective To determine the effects of late surfactant on respiratory outcomes determined at one-year corrected age In the Trial of Late Surfactant (TOLSURF), which randomized extremely low gestational age newborns (ELGAN, ≤28 weeks’ gestational age) ventilated at 7–14 days to late surfactant and inhaled nitric oxide versus inhaled nitric oxide-alone (control). Study design Caregivers were surveyed in a double-blinded manner at 3, 6, 9 and 12 months corrected age to collect information on respiratory resource… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 38 publications
1
39
0
1
Order By: Relevance
“…Our "0.21 by 28" efforts demonstrate that a conscious effort to reduce FiO 2 while maintaining SpO 2 goals in the first 28 days-of-life resulted in improved pulmonary outcomes at 36-weeks PMA. Our results are consistent with a recent study by Wai et al [22], wherein a secondary analysis of the Trial of Late SURFactant to Prevent BPD data demonstrated that a lower cumulative supplemental oxygen exposure at DOL 14 correlated with a lower incidence of BPD or death [24,25]. Similarly, Stevens et al [26] reported that the area under the supplemental oxygen curve at DOL 72-h was a predictor of later respiratory symptoms and need for medications to treat them in very low birthweight infants.…”
Section: Discussionsupporting
confidence: 93%
“…Our "0.21 by 28" efforts demonstrate that a conscious effort to reduce FiO 2 while maintaining SpO 2 goals in the first 28 days-of-life resulted in improved pulmonary outcomes at 36-weeks PMA. Our results are consistent with a recent study by Wai et al [22], wherein a secondary analysis of the Trial of Late SURFactant to Prevent BPD data demonstrated that a lower cumulative supplemental oxygen exposure at DOL 14 correlated with a lower incidence of BPD or death [24,25]. Similarly, Stevens et al [26] reported that the area under the supplemental oxygen curve at DOL 72-h was a predictor of later respiratory symptoms and need for medications to treat them in very low birthweight infants.…”
Section: Discussionsupporting
confidence: 93%
“…Based on evidence that extremely preterm infants exhibit persistent surfactant dysfunction, late or repeated surfactant administration has been explored. Although the TOLSURF trial showed no difference in survival at 36 weeks between infants without BPD receiving late surfactant administration versus no surfactant, there was a trend toward improvement at 40 weeks (with >20% decrease in the number infants requiring respiratory support at 40 weeks) and a substantial decrease in the number of infants who required home respiratory support during the first year 172,173 , an issue that is very important for parents because of the level of stress they experience.…”
Section: Short-term Managementmentioning
confidence: 97%
“…Outcomes such as the need for re-hospitalization, home O2 therapy, and frequent visits to a health care provider or the emergency department in the first years of life have not been systematically reported in most studies, although this is beginning to change (24,25). The use of respiratory medications (e.g.…”
Section: Proposed Endpoints For Clinical Trials That Investigate Cpipmentioning
confidence: 99%